Enhancing Students' Engagement in Learning English Through Non-Digital Gamification - Mardiah, Radiatan; Desi, Desi (English Education : English Journal for Teaching and Learning, 2024)
Abstract    The study investigates the use of non-digital gamification in junior high school English learning, involving seven graders in Jambi Province. The research used Classroom Action Research and two cycles of gamification. Results showed that students found the learning process more interesting and stimulating, with engagement levels significantly increasing. The implementation of each cycle resulted in a 22.5% overall increase in engagement.